The development of Tunisian transport infrastructures under the French protectorate: The foundations of economic dependence (1881-1914) - Vittorio Caligiuri (The Journal of European Economic History (JEEH), 2023)
The development of the Tunisian transport infrastructure in the period following the establishment of the French Protectorate has been little studied. The history of the Tunisian railways and ports is profoundly influenced by developments in the financial situation of the Regency during the last phase of the International Finance Commission, by the peculiar model of development designed by the "colonial pact" as well as by the strategic design of France in the context of the central Mediterranean region. It was precisely in this period that the dependent structure of Tunisian economy was shaped. The economic extroversion of the country was, in fact, precisely the result of the reconfiguration of the mode of insertion of the country in the international capitalism that took place during the period studied in this article. The Tunisian transport infrastructure was both a result and a determining factor of this reconfiguration exerting its persisting effects during the 20th century. The history of the infrastructure development, moreover, allows us to identify the importance of the debt question in the establishment of French administration, the dynamics and drives that accompanied the extension of the mode of production and of capitalist economy in the context of the Tunisian protectorate, but also the redefinition of its integration modalities into international capitalism and the corresponding thrusts in the metropolitan economy.
Keywords: 330; Colonialism; Transportation infrastructure; History; France; Tunisia; Kolonialismus; Verkehrsinfrastruktur; Geschichte; Frankreich; Tunesien